2018
DOI: 10.1007/s00705-018-3774-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening

Abstract: Mayaro fever, caused by Mayaro virus (MAYV) is a sub-lethal disease with symptoms that are easily confused with those of dengue fever, except for polyarthralgia, which may culminate in physical incapacitation. Recently, outbreaks of MAYV have been documented in metropolitan areas, and to date, there is no therapy or vaccine available. Moreover, there is no information regarding the three-dimensional structure of the viral proteins of MAYV, which is important in the search for antivirals. In this work, we const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…These affect early and late stages and morphogenesis, in particular showing the potential application of this new class of antiviral drugs with low cytotoxicity and good bioavailability 75 . In addition, a recent study published by Ferreira et al 76 showed a strong inhibitory effect of epicatechin on MAYV growth, indicating that this is a promising candidate against MAYV.…”
Section: Prevention and Controlmentioning
confidence: 91%
“…These affect early and late stages and morphogenesis, in particular showing the potential application of this new class of antiviral drugs with low cytotoxicity and good bioavailability 75 . In addition, a recent study published by Ferreira et al 76 showed a strong inhibitory effect of epicatechin on MAYV growth, indicating that this is a promising candidate against MAYV.…”
Section: Prevention and Controlmentioning
confidence: 91%
“…Catechins are reported activities against influenza (Song et al, 2005), hepatitis B virus (Li et al, 2001) and docking against ACE2 receptor (Jena et al, 2019). Epicatechin has been reported against Mayaro virus (Ferreira et al, 2018). The antiviral activities of phytochemicals from R. arboreum petal extracts such as Caffeic acid, Kaempferol, Quercetin, Shikimic acid, 4-Coumaric acid and other are tabulated (Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial and antiviral (showed inhibition against Herpes simplex virus type 1 (HSV-1) (Musarra-Pizzo et al, 2019) Anti-oxidant, antitumor, antibacterial, antifungal, antidiabetic, anti-inflammatory, antiproliferative and antitumor (Cosarcã et al, 2019) Antioxidant, UV protective, anti-allergenic, anti-inflammatory, anti-microbial, anti-viral and anti-cancer (Bae et al, 2020) Antiviral (showed inhibition against pandemic influenza A (H1N1) (You et al, 2018) Epicatechin Antiviral (showed inhibitory effect against Mayaro (MAYV) virus and other alphavirus viruses (Ferreira et al, 2018) Antinociceptive and anti-inflammatory (Dias et al, 2018) Antibacterial (Ezhil and Lakshmi, 2017) Antidiabetic (Ibrahim et al, 2018) Anti-infective (Song, 2017) Anti-oxidant, antimicrobial, anti-inflammatory, antitumor, antidiabetic, anticancer and cardioprotective (Prakash et al, 2019) Antioxidant and anticollagenase (showed a high inhibitory power against the collagenase enzyme, responsible for the degradation of matrix collagen and the photo-aging process. (Geeta et al, 2019) UV protection (Prasanth et al, 2020)…”
Section: Catechinmentioning
confidence: 99%